Distance Culture: a chance to participate or a danger of exclusion? Case of people with visual impairment - Dubiel, Monika (Virtualizing the lives of people with disabilities, 2021)
The closure of polish cultural institutions for the public in 2020 forced them to switch their activity to completely virtual mode. It influenced significantly the quality, form and frequency of contact with culture for whole society, but probably it was the biggest change for recipients with disabilities. In this article I analyze the proces of virtualization of culture for its accessibility for people with visual impairment. I investigate possibilities and dangers related to it. The field of my research is the accessible cultural offer of selected institutions and nongovernmental organizations. I collected research data by interviewing both: employees of cultural institutions and recipients with visual impairment. The main research question is: Does virtualization contribute to removing barriers for people with visual impairment in the access to culture or the contrary, deepens already existing problems? Further questions are: how the virtualization impact the frequency of the accessible events and grade of participation of people with visual impairment in them? What kind of innovative solutions appeared in the accessible offer of institutions and organizations? Is the accessibility of distance culture easier or more difficult than in the case of face to face events? Disability studies and accessibility studies serve as a theoretical frame for my considerations.